Practical Application of Nanotechnology Solutions in Pavement Engineering: Construction Practices Successfully Implemented on Roads (Highways to Local Access Roads) Using Marginal Granular Materials Stabilised with New-Age (Nano) Modified Emulsions (NME) - Gerrit J. Jordaan; Wynand J. vdM. Steyn (Applied Sciences, 2022)
The introduction of any new disruptive technology in a traditionally well-established industry, such as the road construction industry, is usually associated with considerable resistance. This is especially relevant when the new technology is based on the use of granular materials traditionally considered to be of an unacceptable quality in combination with relatively new concepts such as New-age (Nano) Modified Emulsions (NME). In such cases, the fact that the material design methods are based on fundamental scientific principles and have been proven in both laboratories and through Accelerated Pavement Testing (APT) may be of little influence. However, the general acceptance of new disruptive technologies, e.g., telecommunications and Information Technologies (IT), have been based on the considerable advantages it presented. The same principles are applicable to the general acceptance and use of the NME stabilisation/enhancement of materials in the road construction industry. This article is aimed at the practical cost-effective demonstration of the general application of the use of nanos-silane-modified emulsions in the construction of the highest order roads, i.e., inter-city multi-lane highways, lower-order roads (including Low-Volume Roads (LVR)), and even local accesses to farms and in villages/townships. The implementation of NME technologies is directly associated with ease of use, time, and cost savings, and with the addressing and reduction of risks applicable to the use thereof.